Heads in beds : a reckless memoir of hotels, hustles, and so-called hospitality - Tomsky, Jacob (New York : Doubleday, 2012)
"A humorous memoir by a veteran hospitality employee that reveals what goes on behind the scenes of the hotel business. Includes tips on how to get the most out of your hotel stay"--Provided by publisher.
Keywords: Tomsky, Jacob; Hotel clerks -- United States -- Biography; Hotels -- Employees -- Biography; Hotels -- United States -- Humor